British Leyland - save it! 1977 (London, 1977)
1977 1974-79 "British Leyland - save it! 1977" [BW0130], 1977, Trades Union Congress British Leyland had been seriously affected by national economic problems plus poor internal industrial relations and went bankrupt in 1975. Sir Don Ryder was asked to undertake an enquiry into the position of the company and following his report the company was partly nationalised in 1975, with the government creating a new holding company called British Leyland Ltd which became BL Ltd (later BL plc) in 1978.